Assessment of Heavy Rainfall using GPM- IMERG Satellite Product over Nepal - Regmi, Nirmala; Nepal, Bikash; Sharma, Shankar; Shrestha, Dibas; Jha, Govind Kumar (Jalawaayu, 2021)
This study evaluates the Integrated Multi-satellite Retrievals from Global Precipitation Measurement (IMERG) final product’s ability to represent the extreme precipitation against 310 observations from Nepal between 2015 and 2017. Additionally, Method of Object-based Diagnostic Evaluation (MODE) analysis was also performed to analyze IMERG ability to capture actual spatial distribution of the rainfall extremes. Both datasets show the extreme rainfall events are mostly concentrated at southern low land areas of the country. MODE tool further revealed the slight shifting of heavy precipitation location by IMERG product as compared to observation. It is also noted that, as precipitation intensity increases (threshold values of rainfall), the number of extreme events decreases. Moreover, this work provides a systematic quantification of the performance of IMERG gauge calibrated product and its applicability in extreme precipitation over mountainous region.